2007
DOI: 10.2307/4122261
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary Cost of Separate Genders Revealed by Male-Limited Evolution

Abstract: Theory predicts that intralocus sexual conflict can constrain the evolution of sexual dimorphism, preventing each sex from independently maximizing its fitness. To test this idea, we limited genome-wide gene expression to males in four replicate Drosophila melanogaster populations, removing female-specific selection. Over 25 generations, male fitness increased markedly, as sexually dimorphic traits evolved in the male direction. When male-evolved genomes were expressed in females, their fitness displayed a nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 0 publications
4
61
3
Order By: Relevance
“…In particular, recessive, sexually antagonistic genes that benefit males should be more likely to accumulate on the X chromosome because they are expressed in the hemizygous sex [31,56]. In a series of experiments on the fruit fly Drosophila melanogaster, the majority of the genome was artificially constrained to be inherited solely though males [24,28,57,58]. Within lines with male-limited inheritance, male fitness increased, while that of females decreased.…”
Section: Tests Of the Sexual Antagonism Hypothesismentioning
confidence: 99%
“…In particular, recessive, sexually antagonistic genes that benefit males should be more likely to accumulate on the X chromosome because they are expressed in the hemizygous sex [31,56]. In a series of experiments on the fruit fly Drosophila melanogaster, the majority of the genome was artificially constrained to be inherited solely though males [24,28,57,58]. Within lines with male-limited inheritance, male fitness increased, while that of females decreased.…”
Section: Tests Of the Sexual Antagonism Hypothesismentioning
confidence: 99%
“…In this case, the intersexual genetic correlation for adult fitness is negative , and it has been shown using experimental evolution that when selection is removed from females, evolved fitness increases in males correspond to equal fitness decreases in females (Prasad et al 2007). Thus, while resolution of conflict over specific shared phenotypic traits may be relatively common, at any one time there may be substantial sexually antagonistic genetic variance for fitness at a genome-wide scale.…”
Section: Genetic Constraints Between the Sexesmentioning
confidence: 99%
“…A number of studies have demonstrated the existence of sexually antagonistic genetic variation for specific traits or components of fitness (Meagher 1992;Rice 1992;Gibson et al 2002;Calsbeek & Sinervo 2004;Fedorka & Mousseau 2004;Pischedda & Chippindale 2006;Prasad et al 2007). Fewer studies have reported estimates of the intersex genetic correlation for lifetime fitness: K0.85 in collared flycatchers (Qvarnström et al 2006); K0.48 in red deer ( Foerster et al 2007); and K0.16 in a laboratory population of Drosophila melanogaster .…”
Section: Introductionmentioning
confidence: 99%